2013
DOI: 10.1088/0031-8949/2013/t152/014001
|View full text |Cite
|
Sign up to set email alerts
|

Halos and related structures

Abstract: The halo structure originated in nuclear physics but is now encountered more widely. It appears in loosely bound, clustered systems where the spatial extension of the system is significantly larger than that of the binding potentials. A review is given on our current understanding of these structures, with an emphasis on how the structures evolve as more cluster components are added, and on the experimental situation concerning halo states in light nuclei.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
211
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(219 citation statements)
references
References 169 publications
6
211
1
1
Order By: Relevance
“…[5][6][7] Such systems do not see details of short-range interactions and their properties can be predicted with any potential that has the same integral properties. Scale invariance noticed in nuclei 5 proved to be applicable also to small atomic clusters.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Such systems do not see details of short-range interactions and their properties can be predicted with any potential that has the same integral properties. Scale invariance noticed in nuclei 5 proved to be applicable also to small atomic clusters.…”
Section: Introductionmentioning
confidence: 99%
“…This discovery has changed the perception of nuclear systems and questioned established knowledge. Although the first anomaly in the expected order of nuclear orbits was observed in 1960 in 11 Be, 18 it was the measurement of the masses of the exotic sodium isotopes, 31,32 Na performed at CERN PS that revealed that these nuclei were tighter bound than expected.…”
Section: Shell Structure: the Decline Of The Magic Numbersmentioning
confidence: 98%
“…8. Many studies have been dedicated to map and define the so-called island of inversion region where 32 Mg is situated in the centre. The 30 Mg (N = 18) isotope has a spherical 0 + ground state with an excited 0 + state at 1788.2 keV.…”
mentioning
confidence: 99%
“…Some indication for decays going directly into the continuum exist for halo nuclei, see [3][4][5] and references therein for details on the halo structure. The two-neutron halo nuclei 6 He and 11 Li appear both to have beta-delayed deuteron emission taking place directly into the continuum [1,6].…”
Section: Beta-particle Decay Mechanismmentioning
confidence: 99%
“…However, this name suggests a two-step process: the beta decay feeding resonance states in the daughter nucleus that subsequently decay by particle emission. The other possible decay mechanism, beta decays feeding the continuum states directly, deserves consideration as well.Some indication for decays going directly into the continuum exist for halo nuclei, see [3][4][5] and references therein for details on the halo structure. The two-neutron halo nuclei 6 He and 11 Li appear both to have beta-delayed deuteron emission taking place directly into the continuum [1,6].…”
mentioning
confidence: 99%